Chemo-enzymatic synthesis of key intermediates (S)-γ-hydroxymethyl-α, β-butenolide and (S)-γ-hydroxymethyl-γ-butyrolactone via lipase-mediated Baeyer–Villiger oxidation of levoglucosenone. Issue 1 (29th September 2014) - Flourat, A. L.; Peru, A. A. M.; Teixeira, A. R. S.; Brunissen, F.; Allais, F.
Abstract : Baeyer–Villiger oxidation of levoglucosenone with CAL-B and solid buffers provided valuable lactones in high yields in only 2 hours while allowing enzyme recyclability. Abstract : Levoglucosenone (LGO ), a valuable chiral platform chemical that can be efficiently produced from catalytic fast pyrolysis of cellulose, has been efficiently converted into optically pure ( S )-γ-hydroxymethyl-α, β-butenolide (HBO ) using a two-step sequence involving a lipase-mediated Baeyer–Villiger oxidation and an acid hydrolysis. In the same fashion, ( S )-γ-hydroxymethyl-γ-butyrolactone (2H-HBO ) was successfully obtained through a three-step sequence (Baeyer–Villiger, palladium-catalysed hydrogenation and acid hydrolysis). The use of solid buffers in the lipase-mediated Baeyer–Villiger oxidation has proved beneficial in two ways: not only the reaction time and the enzymatic load were both reduced four-fold (from 8 to 2 hours and 464 to 113 U mmol −1 ) to reach conversions ≥83%, but solid buffers also prevented lipase from denaturation, thus preserving its enzymatic activity and allowing its use for further oxidation cycles.